Biomechanics of a baseball throw - Hjermstad, I.; Busby, B.; Topp, B.; Anderson, N.
This paper analyzes the activity of throwing a baseball. It compares the performance of an expert and novice thrower. Data was collected through high-speed videotaping and was then reviewed in slow motion to find projection angles and displacement. Using scientific equations, estimations were assigned to acceleration and velocity. By using this process it was found that the baseball was released at a shoulder angle of 237deg and a shoulder velocity of 420 deg/s. The elbow angle was 126 deg and a elbow velocity of 2160 deg/s. The greatest shoulder velocity was 2580 deg/s recorded in frame 13, one frame after the indicated release of the ball while the greatest elbow velocity was 2220 deg/s in frame 6.